Pulmonary cryptococcosis complicated with pulmonary aspergillosis: a series of studies and a literature review - Wang, Xidong; Li, Shaoqiang; Zhu, Mangui; Qiu, Ye; Hui, Yilei; Li, Yongming; Zhan, Yangqing; Wang, Yan; Ye, Feng; Li, Zhengtu (BMC infectious diseases, 2024)
With the development of society, pulmonary fungal diseases, represented by pulmonary aspergillosis and pulmonary cryptococcosis, have become increasingly common. However, there is a lack of clear understanding regarding coinfection by these two types of fungi in immunocompetent individuals. A retrospective study from 2014 to 2022 and a systematic literature review of original articles published in English were performed. Patients with pulmonary cryptococcosis complicated with pulmonary aspergillosis including 5 in the retrospective study and 6 in the systematic literature review. The diagnosis of concurrent pulmonary cryptococcosis and pulmonary aspergillosis in patients was confirmed through repeated biopsies or surgical resection. Pulmonary cryptococcosis is often diagnosed initially (6/11, 55%), while the diagnosis of pulmonary aspergillosis is established when the lesions become fixed or enlarged during treatment. Transbronchial lung biopsy (3/11, 27%), thoracoscopic lung biopsy (2/11, 18%), and percutaneous aspiration biopsy of the lung (1/11, 9%) were the main methods to confirm concurrent infection. Most patients were treated with voriconazole, resulting in a cure for the coinfection (6/11, 55%). Pulmonary cryptococcosis complicated with pulmonary Aspergillus is an easily neglected mixed fungal infection. During the treatment of lesion enlargement in clinical cryptococcus, we need to watch out for Aspergillus infection.